RANCANG BANGUN APLIKASI INFORMASI TRANSPORTASI PUBLIK YOGYAKARTA PADA SISTEM OPERASI ANDROID - , DWINTA RACHMAWATI; , Dr. Azhari SN, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mobile device technology with Android operating system is one of the technology development that gets very good responses from the public. The public interest in the Android operating system is high. It can be determined by the number of variety applications on Android operating system by utilizing the existing features, like GPS and Google Maps. The minimum usage of Android features on the application about public transportation information in Yogyakarta is one of the reason this research conducted. This study talked about developing an application of public transportation information in Yogyakarta on Android operating system that can help the users, especially the people of Yogyakarta in getting information on various types of public transportation that operates in Yogyakarta. Based on the implementation, the application can provide information about various types of public transportion in Yogyakarta, such as taxi, Trans Jogja, citybus, minibus, delman and becak. The information about taxi includes the name of the taxi cab, address and telephone number of the taxi cab service providers that can be contacted directly through the application. The information about Trans Jogja, citybus and minibus includes the route of each fleet in the form of a list or a map, guide lines based on the region of origin and destination that is choosen by the user and information about each type of public transportation. While the information about delman and becak is the marker representing the location of becak and delman and the direction on the map for users to get to the destination.